RANCANG BANGUN ALAT UJI KEAUSAN (TRIBOMETER) DENGAN PENGGERAK MOTOR TIPE XD – 135 - PUTRA PARTAMA (Fakultas Teknik UMRI, 2020)
Every object that moves and comes in contact with one another must experience friction. Friction or commonly referred to as friction is a force that restricts the sliding or rolling motion of an object against another object. The design and manufacturing stage of the tibometer test device, which uses a motor type XD - 135 as a driving force with a maximum load of 98N, knows the dimensions of the components (tribometer) to be made. The design process is carried out by determining the specifications of the equipment to be made, making the design concept of the wear test equipment, making the design of the wear test equipment, the manufacturing process of the wear test equipment. The design and manufacture results in a tibometer test device with specifications of rotation speed 212.12 rpm, linear speed 448.9 mm / s, maximum normal load 98 N, normal force 49 N, stroke length 70mm.